Development and Utilization of Mini Herba Park (Family Medicinal Plant Education Park) as The Instructional Media of Students in RA Miftahul Ulum Arjasa, Jember, East Java - Vivi Liliana Sari; Supeno; Adi Irawan; Mochamad Setiawan (Faculty of Mathematics and Natural Sciences, University of Jember. Jl. Kalimantan No.37, Krajan Timur, Jemberlor, Kec. Sumbersari, Jember Regency, East Java 68121, 2024)
Mini Herba Park (Family Medicinal Plant Education Park) is a program to develop a Toga (Family Medicinal Plant) garden which is used as a learning medium for students at RA Miftahul Ulum. This community service aims to introduce and utilize Toga Park as a instructional media. Methods for implementing this program include conducting initial site surveys and interviews, making program plans, planning learning media and teacher modules, preparing the Mini Herba Park in the form of a place, tools and materials needed as well as other needs, carrying out learning and finally carrying out monitoring and evaluation. The results of this program include a Toga educational park in the school environtment, learning media in the form of accompanying books for teachers and students who have registered with HKI.